Analysis of Hardness, Microstructure, Macrostructure, and Fluidity of Al-Si with Eggshell Variation as Binder in Sand Casting - Fitriyanto, Retnaldi; Puspitasari, Poppy; Murdanto, Putut (Journal of Mechanical Engineering Science and Technology (JMEST), 2018)
Metal casting process can be described as the process of making object by melting metal then poured into the desired mould. The mould that is commonly used is sand moulding. Binder which commonly used in sand casting process is bentonite. Bentonite is kind of mineral which can be run out if it is used continuously. The background of this study was to analyse the other binder that could reduce the use of bentonite by utilizing eggshell. This study aimed to analyse the hardness, microstructure, macrostructure, and fluidity of the cast which yielded by using variations of eggshell. The method that used was experimental method with a model of one-shot case study with descriptive analysis. The study result showed that the highest value of fluidity test was found at variation of 7% eggshell and 3% bentonite with hardness value of 180.86 HV. There were found several defects, casting result with variation of 4% eggshell and 3% bentonite found that there were ± 28 pinhole defects and ± 20 open grain defects. There were found ± 65 pinhole defects and ± 30 open grain structure defects in the casting result with variation 7% eggshell and 3% bentonite. The casting result with variation 10% eggshell and 3% bentonite had ± 50 pinhole defects and ± 30 open grain structure defects.